Smart Irrigation Pump Based on Solar Cell (SIAP BOS) to Improve Agriculture prodution Rainless Land in Sallasae - Aqsha, Ismail; Labusab, Labusab; Danial, Mohammad Ikbal Riski A.; Jayanegara, Sudarmanto; Anwar, Fahri (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2025)
The Community Service Program (PKM) aims to empower the Ulu Galung 1 Farmer Group in Salassae Village, Bulukumba Regency through the implementation of a rice field irrigation system using a solar-powered water pump. The implementation stage method, namely the first stage is conducting initial observations to see the condition of the Ulu Galung 1 farmer group partners at the location to identify problems experienced by partners. The results of the discussion are formulated solutions to solve problems by selecting the right technology and then the process of designing or designing the tool. The second stage of socialization is carried out to provide understanding to the community and farmers about Smart Irrigation Pump technology that uses solar power. The third stage of training is carried out to improve farmers' abilities in using and maintaining equipment. The fourth stage is the application of Solar Cell-based Smart Irrigation Pump technology on agricultural land which is an irrigation solution. The fifth stage is mentoring to provide support to partners/farmers so that the irrigation system works optimally and conducts evaluations of the benefits of irrigation technology and ensures the sustainability of the program.